Generation of micron-sized droplet streams by high frequency electric fields. (December 2019) - Nampoothiri, Krishnadas Narayanan; Bobji, M.S.; Sen, Prosenjit
Graphical abstract: Highlights: Phenomenon behind droplet streams under high frequency electric fields is explored. Streams are due to condensation on nucleation sites from the leakage currents. Microdroplets in droplet stream are dragged along with the air convection currents. Stream velocity increases with electric field. Abstract: Generation and transfer of micron-sized droplets are of significant interest for several applications such as electronics cooling, lab-on-chip, microscale printing, etc. We report generation of microscale droplet streams when a larger droplet is exposed to high frequency (>10 kHz) electric fields using dielectric covered coplanar electrodes. Generation of these droplet streams is found to be a function of the actuation frequency and voltage. Our experiments rule out electrospray as the relevant mechanism. Experiments further reveal that the droplet streams are formed due to (1) Evaporation of the larger droplet due to Joule heating; and (2) Enhanced localized condensation on nucleation sites originating from the leakage currents at high electric fields. The condensed droplets are dragged along with the convection current of the larger droplet, leading to the observation of streams. A computational model is used to solve for the convection velocities which is compared with the experimental high-speed videos. The stream velocity is found to increase with the applied field, which is attributed to the smaller size of the condensed droplet at higher electric fields. Capability to generate microscale droplets and transfer them to other substrates is desired in current microfluidic platforms for various applications. This study reports a viable technique and presents critical information for its design.